Microstructural Characterization of Beryllium Treated Al-Si Alloys - M. F. Ibrahim; S. A. Alkahtani; Kh. A. Abuhasel; F. H. Samuel (Advances in Materials Science and Engineering)
The present study was carried out on B356 and B357 alloys using the thermal analysis technique. Metallographic samples prepared from these castings were examined using optical microscopy and FESEM. Results revealed that beryllium causes partial modification of the eutectic Si, similar to that reported for magnesium additions. Addition of 0.8 wt.% Mg reduces the eutectic temperature by ~10°C. During solidification of alloys containing high levels of Fe and Mg, but no Sr, formation of a Be-Fe phase was detected at 611°C, close to that of α-Al. The Be-Fe phase precipitates in script-like form at or close to the β-Al5SiFe platelets. A new reaction, composed of fine particles of Si and π-Fe phase, was observed to occur near the end of solidification in high Mg-, high Fe-, and Be-containing alloys. The amount of this reaction decreased with the addition of Sr. Occasionally, Be-containing phase particles were observed as part of the reaction. Addition of Be has a noticeable effect on decreasing the β-Al5FeSi platelet length; this effect may be enhanced by addition of Sr. Beryllium addition also results in precipitation of the β-Al5FeSi phase in nodular form, which lowers its harmful effects on the alloy mechanical properties.